A quartz crystal microbalance humidity sensor and its preparation method and monitoring system

By using copper oxide nanofibers as the humidity sensitive layer and combined with a bionic self-cleaning layer, the problem of poor stability of existing quartz crystal microbalance humidity sensors is solved, and a high sensitivity and high stability humidity sensing effect is achieved.

CN119334821BActive Publication Date: 2025-03-18HUBEI UNIV OF TECH

Patent Information

Application Number
CN202411861902.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-18
Estimated Expiration
2044-12-17

AI Technical Summary

Technical Problem

The existing quartz crystal microbalance humidity sensors have poor stability, and the sensing materials are prone to failure in humidity or high temperatures, resulting in poor sensitivity and response speed.

Method used

Copper oxide nanofibers with a diameter of 50-500 nm and a surface roughness <20 nm are used as the humidity-sensitive layer, and a bionic self-cleaning layer is formed on its surface, including a micro-pit array of hydrophobic materials to improve the stability and service life of the sensor.

Benefits of technology

It realizes high sensitivity and high stability humidity sensing, the sensor responds quickly to humidity, has almost no performance attenuation, and has significantly improved service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119334821B_ABST
    Figure CN119334821B_ABST
Patent Text Reader

Abstract

The present invention discloses a quartz crystal microbalance humidity sensor and a preparation method and monitoring system thereof, which belong to the field of intelligent sensors. The sensor comprises a quartz crystal microbalance, and a crystal oscillator electrode surface on one side of the quartz crystal microbalance is provided with a humidity sensitive layer; the humidity sensitive layer is composed of copper oxide nanofibers with a diameter of 50-500nm and a surface roughness of <20nm. The copper oxide nanofiber surface of the humidity sensitive layer of the sensor constructed by the present invention has abundant oxygen vacancies, which is conducive to the adsorption of water molecules, thereby effectively changing the surface mass load of the quartz crystal microbalance, and the metal oxide CuO is relatively stable in the air; in addition, the sensor has a sensitivity of 82.5±7.7 Hz / relative humidity and a stability of almost no performance degradation for 15 days.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of intelligent sensors, and in particular to a quartz crystal microbalance humidity sensor and a preparation method and a monitoring system thereof. Background Art

[0002] With the rapid development of science and technology, environmental monitoring technology, as an important means to protect human health and sustainable production, is gaining increasing attention. Humidity monitoring is an important part of environmental monitoring and is crucial for medical diagnosis, drug transportation, food storage, agricultural production, semiconductor manufacturing and other fields. Therefore, it is necessary to develop humidity sensors with high sensitivity, fast response and good stability.

[0003] The quartz crystal microbalance is a highly sensitive micromass sensing platform that can provide nanogram-level accuracy. Specific sensitive materials modified on its surface can be used for highly sensitive humidity monitoring, such as two-dimensional materials, metal oxides, polymers, metal organic frameworks, and fiber composites. However, a large number of sensing materials (such as polymers and salts) will expand when wet, and some sensing materials (such as hydroxides and polymers) are easily decomposed by heat, resulting in failure of the sensitive layer and poor sensor stability.

[0004] Therefore, it is necessary to construct a quartz crystal microbalance humidity sensor with strong stability. Summary of the invention

[0005] In order to solve the problems existing in the prior art, the present invention provides a quartz crystal microbalance humidity sensor, comprising a quartz crystal microbalance, wherein a humidity sensitive layer is arranged on the surface of a crystal oscillator electrode on one side of the quartz crystal microbalance;

[0006] The humidity sensitive layer is composed of copper oxide nanofibers with a diameter of 50-500nm and a surface roughness of less than 20nm.

[0007] Furthermore, a bionic self-cleaning layer is also provided on the surface of the humidity sensitive layer.

[0008] Furthermore, the bionic self-cleaning layer is a hydrophobic material micro-pit array with a line width of 3-20 μm, a line spacing of 25-100 μm, and a thickness of 40-50 μm.

[0009] The bionic self-cleaning layer forms a closed air microcavity, and water droplets falling on the bionic self-cleaning layer can bounce back quickly and take away pollutants on the sensor surface, thereby effectively improving the service life of the humidity sensor. In the present invention, the hydrophobic material does not need to be strictly limited and can be a photoresist, etc.

[0010] It should be noted that, in the present invention, the material of the crystal oscillator electrode does not need to be strictly limited, and can be any solid metal, illustratively, gold, silver, etc.

[0011] The present invention also provides a method for preparing a quartz crystal microbalance humidity sensor, comprising:

[0012] A copper seed layer is prepared on the surface of the crystal electrode on one side of the quartz crystal microbalance, and then placed in an alkaline etching solution to grow the copper seed layer into copper hydroxide nanowires;

[0013] A quartz crystal microbalance with copper hydroxide nanowires on the surface of a crystal oscillator electrode on one side is heat treated, and the copper hydroxide nanowires are converted into copper oxide nanofibers with a diameter of 50-500nm and a surface roughness of <20nm.

[0014] Further, the alkaline etching solution comprises an alkaline substance and an etchant at a molar concentration ratio of 5-50:1;

[0015] The alkaline substance includes at least one of sodium hydroxide and potassium hydroxide;

[0016] The etchant includes at least one of ammonium persulfate and ammonium thiosulfate.

[0017] Preferably, the concentrations of potassium hydroxide and ammonium persulfate in the alkaline etching solution are 0.375 mol / L and 0.015 mol / L respectively. The solvent of the alkaline etching solution is preferably water.

[0018] Furthermore, the growth time of the copper hydroxide nanowires is 5-15 minutes. Preferably, the growth process is carried out in a vibration-free environment, and a damping isolation platform or an air floating platform can be used.

[0019] Furthermore, the heat treatment is continued at a temperature of 100-500° C. for 15-35 minutes.

[0020] Furthermore, the copper seed layer is prepared by magnetron sputtering or electron beam evaporation.

[0021] Preferably, the magnetron sputtering power is 50-100 W, more preferably 50 W; the electron beam evaporation rate is 0.2-0.5 kÅ / s, more preferably 0.2 kÅ / s.

[0022] Furthermore, the copper seed layer has a thickness of 150-300 nm.

[0023] Preferably, the copper seed layer has a thickness of 200 nm.

[0024] When the area of ​​the copper seed layer is too small, the sensor sensitivity will be reduced, and when the deposition area is too large, the quartz crystal microbalance will not vibrate easily; at the same time, for a certain area of ​​the copper seed layer, different shapes have little effect on the sensitivity. Therefore, the shape of the copper seed layer does not need to be strictly limited, and can be square, circular, other polygonal or irregular shapes, etc.

[0025] Preferably, the area of ​​the copper seed layer is 50-100 mm 2 , the preferred shape is a circle with a diameter of 8-10 mm.

[0026] The present invention also provides a detection system, comprising the above-mentioned quartz crystal microbalance humidity sensor.

[0027] The principle of the present invention is to deposit copper on the surface of the crystal electrode on one side of the quartz crystal microbalance, etch to form copper hydroxide, and then adjust the heat treatment conditions to prepare copper oxide material in situ as a humidity sensitive layer. The heat treatment temperature has a significant effect on the ratio of the amount of adsorbed oxygen to the amount of lattice oxygen of copper oxide, that is, oxygen vacancies, and the heat treatment time will significantly affect the adsorption of water molecules by copper oxide. The copper oxide sensor prepared based on appropriate heating temperature and time has higher response and sensitivity for humidity detection, which can be significantly better than the copper hydroxide-based sensor that has not been heat treated.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] The copper oxide nanofiber surface of the humidity sensitive layer of the sensor constructed by the present invention has abundant oxygen vacancies, which is conducive to the adsorption of water molecules, thereby effectively changing the surface mass load of the quartz crystal microbalance. At the same time, the metal oxide CuO is relatively stable in the air; in addition, the sensor has a sensitivity of 82.5±7.7 Hz / relative humidity and a stability of almost no performance degradation for 15 days. Overall, the sensor constructed by the present invention has the characteristics of high sensitivity and high stability, and has a good industrialization prospect. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0031] Figure 1 The structure diagram of the humidity sensor constructed by the present invention is shown;

[0032] Figure 2 The scanning electron microscope image of the copper seed layer prepared by the magnetron sputtering method in Example 1 is shown;

[0033] Figure 3 shows a scanning electron microscope image of a copper seed layer prepared by electron beam evaporation in Example 2;

[0034] Figure 4 shows a scanning electron microscope image of copper oxide nanowires prepared in Example 1;

[0035] Figure 5 An optical interferometer measurement diagram of copper oxide nanowires prepared in Example 1 is shown;

[0036] Figure 6 The oxygen vacancy test diagram of the copper oxide nanowires prepared in Example 1 is shown;

[0037] Figure 7 The response results of the sensor constructed in Example 1 under different relative humidity are shown;

[0038] Figure 8 Shows Figure 7 The fitting results of

[0039] Fig. 9 The results of the sensitivity of the sensors constructed in Examples 5 to 7 and Comparative Example 1 relative to the sensitivity of Example 1 are shown;

[0040] Fig.10 The response amplitude variation diagram of the sensors constructed in Example 1, Example 8 to Example 12 under the same relative humidity is shown;

[0041] Fig.11 The mass change of the material of the humidity sensitive layer of the sensor constructed in Example 1 at 25-200°C is shown;

[0042] Fig.12 The mass change of the material of the humidity sensitive layer of the sensor constructed in Comparative Example 1 at 25-200° C. is shown;

[0043] Fig.13 The response results of the sensor constructed in Example 1 at different storage times and different relative humidity are shown;

[0044] Fig.14 A scanning electron microscope image showing the structure of the bionic self-cleaning layer of the sensor constructed in Example 1;

[0045] Fig.15 The results of the water contact angle obtained by adjusting the line width and line spacing of the micropit array in Example 13 are shown;

[0046] Fig.16The super-hydrophobic simulation result diagram of the sensor constructed in Example 1 is shown, wherein (a), (b), (c), (d) and (e) respectively represent simulation diagrams of the time extension of a water droplet falling on the surface of the super-hydrophobic layer;

[0047] Fig.17 The pictures of superhydrophobic test and self-cleaning test of the sensor constructed in Example 1 are shown, wherein (a1), (a2), (a3), (a4), (a5), (a6), (a7), (a8), (a9), (a10) represent the pictures of the time when the water droplets fall onto the horizontally placed clean sensor surface, which are 0ms, 1ms, 2ms, 3ms, 4ms, 5ms, 6ms, 8ms, 10ms and 12ms, respectively, and (b1), (b2), (b3), (b4), (b5), (b6), (b7), (b8), (b9), (b10) represent the time when the water droplets fall onto the horizontally placed dusty sensor surface, which are 0ms, 1ms, 2ms, 3ms, 5ms, 7ms, 9ms, 11ms, 12ms, respectively. The photos of (c1), (c2), (c3), (c4), (c5), (c6), (c7), (c8), (c9), and (c10) show the times when water drops fall onto the surface of a clean sensor tilted at 45°, which are 0ms, 1ms, 2ms, 3ms, 4ms, 5ms, 6ms, 8ms, 10ms, and 12ms, respectively; the photos of (d1), (d2), (d3), (d4), (d5), (d6), (d7), (d8), (d9), and (d10) show the times when water drops fall onto the surface of a dusty sensor tilted at 45°, which are 0ms, 1ms, 2ms, 3ms, 5ms, 7ms, 9ms, 11ms, 13ms, and 15ms, respectively. DETAILED DESCRIPTION

[0048] The endpoints and any values ​​of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.

[0049] The following will be combined with the specific embodiments of the present invention and the drawings of the specification to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0050] Example 1

[0051] A kind of Figure 1 The quartz crystal microbalance humidity sensor shown in the figure has the following steps for its preparation:

[0052] (1) Using anhydrous ethanol and deionized water for ultrasonic cleaning for 15 min each, and then using oxygen plasma cleaning for 45 s to clean the quartz crystal microbalance to enhance the surface adhesion of the crystal electrode, wherein the material of the crystal electrode is gold;

[0053] (2) Covering the patterned mask on the surface of the crystal oscillator electrode on one side of the quartz crystal microbalance, and then using a magnetron sputtering instrument, setting the sputtering power to 50 W and the sputtering time to 10 min, growing a copper seed layer on the side with the mask, and removing the mask after completion to prepare a circular copper seed layer with a thickness of about 200 nm and a diameter of 8.5 mm;

[0054] (3) The quartz crystal microbalance with the copper seed layer was placed in a mixed aqueous solution of 0.375 mol / L potassium hydroxide and 0.015 mol / L ammonium persulfate, and grown on a damping isolation table for 10 min to convert the copper seed layer into copper hydroxide nanowires. The product was then fished out, cleaned, dried at 25°C, and annealed in an air atmosphere at 200°C for 15 min to in situ convert the copper hydroxide nanowires into copper oxide nanowires to form a humidity sensitive layer.

[0055] (4) SU8 photoresist with a thickness of 50 nm was spin-coated on the surface of the humidity sensitive layer. After the pre-bake, the excess photoresist was removed with acetone, leaving a circular area with a diameter of about 9 mm. Subsequently, photolithography, post-bake and development were performed to obtain a micro-pit array with a line width of 5 μm, a line spacing of 50 μm and a thickness of 50 μm, thus forming a bionic self-cleaning layer.

[0056] Example 2

[0057] The method is basically the same as Example 1, except that the material of the crystal oscillator electrode of the quartz crystal microbalance selected in step (1) is silver.

[0058] Example 3

[0059] The method is basically the same as Example 1, except that: in step (2), the copper seed layer is prepared by electron beam evaporation, and the specific parameter is that the electron beam evaporation rate is 0.2 kÅ / s.

[0060] Example 4

[0061] The method is basically the same as Example 1, except that in step (2), a square copper seed layer with a thickness of about 200 nm and a side length of 8.5 mm is prepared, and accordingly, a square area with a side length of about 9 mm is retained in step (4).

[0062] Example 5-Example 7

[0063] The method is basically the same as Example 1, except that in step (3), annealing is performed in an air atmosphere at 100°C, 300°C, and 400°C for 15 min respectively.

[0064] Examples 8-12

[0065] The method is basically the same as Example 1, except that: in step (3), the annealing is performed in an air atmosphere at 200° C. for 10 min, 20 min, 25 min, 30 min, and 40 min, respectively.

[0066] Embodiment 13

[0067] The method is basically the same as Example 1, except that the line width and line spacing of the micro-pit array are adjusted.

[0068] Comparative Example 1

[0069] A method for preparing a quartz crystal microbalance humidity sensor, the steps are as follows:

[0070] (1) Using anhydrous ethanol and deionized water for ultrasonic cleaning for 15 min each, and then using oxygen plasma cleaning for 45 s to clean the quartz crystal microbalance to enhance the surface adhesion of the crystal electrode, wherein the material of the crystal electrode is gold;

[0071] (2) Covering the patterned mask on the surface of the crystal oscillator electrode on one side of the quartz crystal microbalance, and then using a magnetron sputtering instrument with a power of 50 W and a time of 10 min to grow a copper seed layer on the side with the mask, and then removing the mask to prepare a circular copper seed layer with a thickness of about 200 nm and a diameter of 8.5 mm;

[0072] (3) placing the quartz crystal microbalance with the copper seed layer in a mixed aqueous solution of 0.375 mol / L potassium hydroxide and 0.015 mol / L ammonium persulfate, growing it on a damping isolation table for 10 min, converting the copper seed layer into copper hydroxide nanowires, then fishing out the product, washing it, and drying it at 25°C to form a humidity sensitive layer;

[0073] (4) SU8 photoresist with a thickness of 50 nm was spin-coated on the surface of the humidity sensitive layer. After the pre-bake, the excess photoresist was removed with acetone, leaving a circular area with a diameter of about 9 mm. Subsequently, photolithography, post-bake and development were performed to obtain a micro-pit array with a line width of 5 μm, a line spacing of 50 μm and a thickness of 50 μm, thus forming a bionic self-cleaning layer.

[0074] Test Case

[0075] The morphologies of the copper seed layers obtained in the preparation process of Example 1 and Example 3 were observed by scanning electron microscope. Figure 2 and Figure 3 As shown in FIG. 1 , it can be seen that the copper particles in the copper seed layer prepared by magnetron sputtering are larger and more uniform than those prepared by electron beam evaporation. The morphology of the copper oxide nanowires prepared in Example 1 was also observed by scanning electron microscopy, as shown in FIG. Figure 4 As shown, it can be seen that the copper oxide nanowires present a spatially stacked fiber bundle structure, and the diameter of the fiber bundle is about 100-500nm. The roughness of the copper oxide nanowires was also tested using an optical interferometer, and the results are shown in Figure 5 As shown in Figure 2, the roughness of the copper oxide nanowires is 18 nm. The oxygen vacancies of the copper oxide nanowires at different annealing temperatures were also tested, such as Figure 6 As shown, it can be seen that at 150°C, the ratio of the number of adsorbed oxygen to the number of lattice oxygen is moderate, which may be beneficial to improving the sensitivity of the sensor.

[0076] The response results of the sensor constructed in Example 1 were tested at different relative humidity. Figure 7 As shown, it can be seen that it has a sensitivity of 82.5±7.7 Hz / relative humidity. Figure 8 As shown, the logarithm of relative humidity and frequency difference with natural numbers as the base shows a good linear relationship: ln frequency difference = 0.098 + 0.03856 relative humidity. The response results of the sensors constructed in Examples 5 to 7 and Comparative Example 1 were also tested in the same humidity range, and the sensitivity was fitted and compared with that in Example 1. The results are as follows: Fig. 9 As shown (it should be noted that comparative example 1 does not have an annealing process, but is simply dried at 25°C), it can be seen that compared to comparative example 1, the sensors of examples 1 and 6 have better sensitivity, while the relative sensitivity of example 7 with a higher annealing temperature is significantly reduced. The response results of the sensors constructed in examples 1, 8 to 12 were also tested in the same humidity range, as shown in FIG. Fig.10 As shown in the figure, it can be seen that Example 1 annealed at 200°C for 15 min has a higher frequency change amplitude. These results show that both the annealing temperature and time affect the sensitivity of the constructed sensor. Figure 6 The oxygen vacancies of the copper oxide nanowires have a suitable ratio of the number of adsorbed oxygen to the number of lattice oxygen after annealing at 200°C for 15 minutes, thus significantly improving the sensitivity of the constructed sensor to humidity. This is because CuO will produce a large number of oxygen vacancies during the annealing process. The number of surface oxygen vacancies increases with the increase of annealing temperature, reaching a maximum value at 200°C and then decreasing. This change trend is consistent with the sensitivity change trend. These vacancies provide more adsorption sites, the adsorption process is more intense, and water molecules are strongly adsorbed to the sensor surface. This is the main factor that the sensor of the present invention has high sensitivity.

[0077] For sensors, in addition to high sensitivity, high stability is also very important. The materials of the humidity sensitive layer of the sensors of Example 1 and Comparative Example 1 were heated at 25-200°C. The results are as follows: Fig.11 and Fig.12 As shown. It can be seen that the copper hydroxide of comparative example 1 undergoes a mass mutation due to oxidation and dehydration at around 150°C, while the mass change of the copper oxide of example 1 is not obvious. The irreversible mass mutation of copper hydroxide will cause the sensor to fail at high temperatures, limiting its application to low temperatures. The sensor constructed by the present invention can be used in a wider temperature range and can meet general test environments.

[0078] A group of sensors were prepared in parallel using the preparation method of Example 1. These sensors were stored for 2 days, 9 days and 15 days, and the response analysis was performed under different relative humidity. The results are as follows: Fig.13 As shown, it can be seen that the sensor constructed by the present invention has good stability, and the signal does not decrease significantly even after being stored for 15 days.

[0079] Fig.14 The structure of the bionic self-cleaning layer of the sensor constructed in Example 1 is shown. Fig.15 The water contact angle obtained by testing the micropit array after adjusting the line width and line spacing of Example 13 is shown. It can be seen from the figure that when the thickness is 50μm, the line width is about 5-15μm and the line spacing is about 40-60μm. The water contact angle of the bionic self-cleaning layer is larger, and the constructed sensor is more hydrophobic. The bionic self-cleaning layer of Example 1 belongs to this range, and the sensor constructed in Example 1 has strong hydrophobicity.

[0080] Fig.16 The simulation results of pressure change when a water droplet falls on the surface of the super-hydrophobic layer are shown, where (a), (b), (c), (d) and (e) are simulation diagrams of the water droplet falling on the surface of the super-hydrophobic layer for an extended period of time. These results indicate that the micro-pit array of the bionic self-cleaning layer can form a closed air micro-cavity with a certain pressure when contacting the droplet, making the sensor surface have super-hydrophobic properties. Fig.17 A photograph of a water drop falling on the surface of the sensor constructed in Example 1 is shown. It can be seen that the drop bounces back quickly on the surface of the bionic self-cleaning layer within 15ms, which can remove dust on the sensor surface, thereby achieving self-cleaning of the device and increasing the service life of the sensor.

[0081] In summary, the copper oxide nanofiber surface of the humidity sensitive layer of the sensor constructed by the present invention has abundant oxygen vacancies, which is conducive to the adsorption of water molecules, thereby effectively changing the surface mass load of the quartz crystal microbalance, and copper oxide also has high environmental stability; in addition, the sensor has a sensitivity of 82.5±7.7 Hz / relative humidity, a fast response time of less than 1s, and a stability of almost no performance degradation for 14 days. Overall, the sensor constructed by the present invention has the characteristics of high sensitivity, fast response, and high stability, and has a good prospect for industrialization.

[0082] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A quartz crystal microbalance humidity sensor, comprising a quartz crystal microbalance, characterized in that: A humidity sensitive layer is provided on the surface of the crystal oscillator electrode on one side of the quartz crystal microbalance; The humidity sensitive layer is composed of copper oxide nanofibers with a diameter of 50-500nm and a surface roughness of less than 20nm; The surface of the humidity sensitive layer is also provided with a bionic self-cleaning layer; The bionic self-cleaning layer is a hydrophobic material micro-pit array with a line width of 3-20 μm, a line spacing of 25-100 μm, and a thickness of 40-50 μm.

2. A method for preparing the quartz crystal microbalance humidity sensor according to claim 1, characterized in that: include, A copper seed layer is prepared on the surface of a crystal oscillator electrode on one side of a quartz crystal microbalance, and then placed in an alkaline etching solution to grow the copper seed layer into copper hydroxide nanowires; A quartz crystal microbalance with copper hydroxide nanowires on the surface of a crystal oscillator electrode on one side is subjected to heat treatment, and the copper hydroxide nanowires are converted into copper oxide nanofibers with a diameter of 50-500 nm and a surface roughness of <20 nm; Preparation of hydrophobic material micro-pit arrays on the surface of copper oxide nanofibers.

3. The method for preparing the quartz crystal microbalance humidity sensor according to claim 2, characterized in that: The alkaline etching solution comprises an alkaline substance and an etchant at a molar concentration ratio of 5-50:1; The alkaline substance includes at least one of sodium hydroxide and potassium hydroxide; The etchant includes at least one of ammonium persulfate and ammonium thiosulfate.

4. The method for preparing the quartz crystal microbalance humidity sensor according to claim 2, characterized in that: The growth time of the copper hydroxide nanowires is 5-15 minutes.

5. The method for preparing the quartz crystal microbalance humidity sensor according to claim 2, characterized in that: The heat treatment lasts for 10-40 minutes at a temperature of 100-500°C.

6. The method for preparing the quartz crystal microbalance humidity sensor according to claim 2, characterized in that: The copper seed layer is prepared by magnetron sputtering or electron beam evaporation.

7. The method for preparing the quartz crystal microbalance humidity sensor according to claim 6, characterized in that: The copper seed layer has a thickness of 150-300 nm.

8. A detection system, characterized in that: It comprises the quartz crystal microbalance humidity sensor as claimed in claim 1.

Citation Information

Patent Citations

  • Copper-oxide-decorated quartz crystal microbalance sensor having opposite response signals for hydrogen cyanide gas and water vapor

    CN104181068A

Cited By

  • Annular electrode type piezoelectric quartz crystal humidity sensor

    CN223400757U

  • Gold electrode piezoelectric quartz crystal humidity sensor

    CN223664458U